Advanced magnetic resonance spectroscopic neuroimaging: Experts' consensus recommendations. (29th April 2020) - Maudsley, Andrew A.; Andronesi, Ovidiu C.; Barker, Peter B.; Bizzi, Alberto; Bogner, Wolfgang; Henning, Anke; Nelson, Sarah J.; Posse, Stefan; Shungu, Dikoma C.; Soher, Brian J.
Abstract : Magnetic resonance spectroscopic imaging (MRSI) offers considerable promise for monitoring metabolic alterations associated with disease or injury; however, to date, these methods have not had a significant impact on clinical care, and their use remains largely confined to the research community and a limited number of clinical sites. The MRSI methods currently implemented on clinical MRI instruments have remained essentially unchanged for two decades, with only incremental improvements in sequence implementation. During this time, a number of technological developments have taken place that have already greatly benefited the quality of MRSI measurements within the research community and which promise to bring advanced MRSI studies to the point where the technique becomes a true imaging modality, while making the traditional review of individual spectra a secondary requirement. Furthermore, the increasing use of biomedical MR spectroscopy studies has indicated clinical areas where advanced MRSI methods can provide valuable information for clinical care. In light of this rapidly changing technological environment and growing understanding of the value of MRSI studies for biomedical studies, this article presents a consensus from a group of experts in the field that reviews the state‐of‐the‐art for clinical proton MRSI studies of the human brain, recommends minimal standards for further development of vendor‐provided MRSI implementations, and identifies areas which need further technical development. Abstract : MR spectroscopic imaging enables noninvasive mapping of metabolites within the body and offers considerable potential for clinical and biomedical research studies. Recent technological advances, in high‐field MRI instrumentation, spatial‐spectral sampling and image reconstruction methods, and data analysis, have greatly improved spatial resolution and the extent of the brain over which metabolites can be mapped. This consensus statement summarizes the state‐of‐the‐art for clinical MRSI studies of the brain and provides a set of implementation standards matched to different clinical applications.